COMMUNITY SERVICE ACTIVITIES USING EXPERIMENTAL SIMULATIONS AND PHYSICS LEARNING MEDIA - Angelina Rahma; Maria Lidya Tanggo; Dominika Owa; Yasinta Embu Ika; Aloisius Harso; Melkyanus Bili Umbu Kaleka (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
Physics learning at SMA Negeri 1 Riung Barat faces real obstacles in the form of limited laboratory facilities and a lack of practical tools, so the learning process tends to be theoretical and makes it difficult for students to understand abstract concepts. This community service activity aims to improve the quality of physics learning using experimental simulations and innovative teaching aids, improving conceptual understanding, experimental skills, and fostering student learning motivation. The activity was carried out on May 23, 2026, targeting students in grades X, XI, and XII, and physics teachers. The implementation method included a preparation stage (survey and coordination), followed by socialization and interactive demonstrations of various alternative media such as static electricity teaching aids, hydraulic pumps, and rigid body equilibrium. After the demonstration, students carried out direct practice in small groups with the guidance of the community service team and teachers. Evaluation was carried out through observation of involvement and distribution of participant response questionnaires. The results of the activity showed an increase in students' conceptual understanding and experimental skills. The performance evaluation recorded an increase in the ability to use teaching aids from the "Low" to "Good" category, and observation and measurement skills increased from the "Fair" to "Good" category. In addition, the level of student activity jumped from the "Medium" to the "High" category. Ninety-two per cent of participants expressed great satisfaction with the program. As a form of sustainability, the program produced outputs in the form of simple experiment modules, video documentation for dissemination, and a guide to using teaching aids to support teachers in independently implementing lab-based learning.